Study on Self-Adaptive Message Scheduler Used for the Vehicle Ad-hoc Network - 刘明剑(MINGJIAN LIU); 谭国真(GUOZHEN TAN); 丁男(NAN DING); 张福新(FUXIN ZANG) (Journal of Information Science and Engineering, 2017)
To satisfy the strict demands of VANET (vehicular ad-hoc network) on communication rate, response speed as well as on reliability, a communication sublayer that provides reliable, real-time and qualified communication services for upper applications is constructed in VANET. By using the queuing theory and based on researching the message queues in VANET, the current study designed a scheme for optimizing the communication sublayer, and proposed mechanisms for message compression, sending-frequency self-adaption as well as for data transmission compression, which make up an easy-to-bedeployed framework that provides safe, real-time and standard self-adaptive communication services for upper applications and which solve the problem that previous VANET communication is not reliable and real-time. Through simulation and real vehicle experiments ,we verify that the design can well satisfy the communication requirements of VANET in terms of performance and functionality, bandwidth occupancy decrease by 47.8 % and 11.4% relatively compared with CMS (common message set) and unoptimized MD (message dispatcher) decreased ,compared with CMS and unoptimized MD, the transmission frequency can decrease by 60% and 6.1%, and data compression ratio is 12.3%, thus proving the effectiveness of our scheme.